Angiotensin II type 2 receptor and receptor Mas are colocalized and functionally inter-dependent in obese Zucker rat kidney - Patel, Sanket N. (Hypertension, 2017)
The actions of angiotensin II type 2 receptor (AT(2)R) and the receptor Mas (MasR) are complex but show similar pro-natriuretic function; particularly AT(2)R expression and natriuretic function are enhanced in obese/diabetic rat kidney. In light of some reports suggesting a potential positive interaction between these receptors, we tested hypothesis that renal AT(2)R and MasR physically interact and are inter-dependent to stimulate cell signaling and promote natriuresis in obese rats. We found that infusion of AT(2)R agonist C21 in obese Zucker rats (OZR) increased urine flow (UF) and urinary Na-excretion (UNaV) which were attenuated by simultaneous infusion of the AT(2)R antagonist PD123319 or the MasR antagonist A-779. Similarly, infusion of MasR agonist Ang-(1-7) in OZR increased UF and UNaV, which were attenuated by simultaneous infusion of A-779 or PD123319. Experiment in isolated renal proximal tubules of OZR revealed that both the agonists C21 and Ang-(1-7) stimulated NO which was blocked by either of the receptor antagonists. Dual-labeling of AT(2)R and MasR in OZR kidney sections and human proximal tubule epithelial cells showed that AT(2)R and MasR are colocalized. The AT(2)R also co-immunoprecipitated with MasR in cortical homogenate of OZR. Immunoblotting of cortical homogenate cross-linked with zero length oxidative (sulfhydryl groups) cross-linker cupric-phenanthroline revealed a shift of AT(2)R and MasR bands upward with overlapping migration for their complexes which were sensitive to the reducing β-mercaptoethanol, suggesting involvement of –SH groups in cross linking. Collectively, the study reveals that AT(2)R and MasR are co-localized and functionally interdependent in terms of stimulating NO and promoting diuretic-natriuretic response.